Impatiens sikaiensis sp. nov. (Balsaminaceae) from Sichuan, China. Issue 2 (15th December 2022) - Ying, Yuan; Hong, Chen; Qiang, Luo
Abstract : Impatiens sikaiensis Q. Luo & Y. Yuan, a new species of the genus Impatiens from Zhaojue County, Sichuan, China, is described in detail with its morphological characteristics, photographs and physical drawings. The species resembles Impatiens uniflora morphologically but can be distinguished from the latter by its yellow flowers; ovate bracts with long‐cuspidate apex, 5–9 mm long; lateral sepals 6–12 mm long; dorsal petals with a narrowly cristate swelling at abaxial mid‐vein, and a rough tip at the apex. The micro‐morphological features and surface patterning of the pollen grains and seeds of the new species were examined using scanning electron microscopy (SEM). This revealed that the pollen grains of the new species typically have 5 angles and 5 germ furrows, which has not before been reported in the species of Impatiens commonly found in China.